Acute renal failure and type B lactic acidosis as first manifestation of extranodal T-cell lymphoblastic lymphoma. (9th June 2014) - Yun, Seongseok; Walker, Courtney N; Vincelette, Nicole D; Anwer, Faiz
Abstract : We describe a rare case of a 19-year-old male patient with a history of epilepsy and developmental delay who presented with acute renal failure (ARF) and lactic acidosis (LA) as the first manifestation of T-cell lymphoblastic lymphoma. Renal ultrasound and CT of the abdomen showed renal parenchymal infiltration, and renal biopsy demonstrated T-cell lymphoblastic lymphoma. LA, ARF and electrolyte abnormalities were refractory to the initial treatment of bicarbonate infusion and hydration. However, these abnormalities rapidly normalised after the initiation of chemotherapy, suggesting that the LA and ARF were secondary to lymphomatous renal infiltration.